2001
DOI: 10.1177/154193120104502314
|View full text |Cite
|
Sign up to set email alerts
|

Annoyance and Urgency of Auditory Alerts for in-Vehicle Information Systems

Abstract: The proliferation of in-vehicle information systems and the need for drivers to keep their eyes on the road suggest that auditory alerts will become increasingly common. This study examined how sound parameters affected perceived urgency and annoyance. The sound parameters investigated were overall density of a warning tone, pulse speed and type of burst used to create a warning tone. The context in which the auditory alert is presented was an additional factor. Significant effects were found for all factors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 3 publications
1
12
1
Order By: Relevance
“…The sound characteristics included the sonic urgency of the collision avoidance warning (defined by varying the burst density and loudness) and of the e-mail alert (defined by varying the onset and offset rates). Sonic urgency refers to the urgency of the sound based on the sound parameters that previous research has shown to influence perceived urgency as measured by subjective ratings or reaction time to warnings (Edworthy et al 1991, Hellier et al 1993, Edworthy and Adams 1996, Marshall et al 2001. In this paper, we refer to sonic urgency as 'urgency' and perceived urgency as referred to as 'rated urgency'.…”
Section: Independent and Dependent Variablesmentioning
confidence: 99%
See 4 more Smart Citations
“…The sound characteristics included the sonic urgency of the collision avoidance warning (defined by varying the burst density and loudness) and of the e-mail alert (defined by varying the onset and offset rates). Sonic urgency refers to the urgency of the sound based on the sound parameters that previous research has shown to influence perceived urgency as measured by subjective ratings or reaction time to warnings (Edworthy et al 1991, Hellier et al 1993, Edworthy and Adams 1996, Marshall et al 2001. In this paper, we refer to sonic urgency as 'urgency' and perceived urgency as referred to as 'rated urgency'.…”
Section: Independent and Dependent Variablesmentioning
confidence: 99%
“…The collision warning was developed and tested for collision warning systems (Lerner 1991, Kiefer et al 1999. The e-mail alert was developed and tested as part of a previous set of experiments (Marshall et al 2001) The sound parameters that we chose to define high and low levels of urgency were those that have shown a strong effect on perceived urgency in previous research (Edworthy andAdams 1996, Marshall et al 2001).…”
Section: Independent and Dependent Variablesmentioning
confidence: 99%
See 3 more Smart Citations